High-strength and high-transparency super-hydrophobic coating constructed based on self-adhesion nanoparticles and rapid preparation technology thereof

By designing the combination of self-adhesive nanoparticles and hydrophobic self-adhesive polymers, the problem of insufficient mechanical strength and transparency of super-hydrophobic coatings is solved, and high-strength and high-transparent coating preparation is achieved, which simplifies the process and is suitable for large-scale Large-scale production.

CN119119782APending Publication Date: 2024-12-13SHANGHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411268987.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing superhydrophobic coatings have shortcomings in terms of mechanical strength and transparency, the preparation process is cumbersome and difficult to meet the needs of large-scale production, and the introduced adhesives will affect the transparency of the coating.

Method used

Designing self-adhesive nanoparticles form spray liquid through the combination of nanoparticles and hydrophobic self-adhesive polymers. Use the spraying process to prepare high-strength, highly transparent superhydrophobic coatings on multiple transparent substrates, avoiding the traditional methods. High temperature treatment and adhesive use.

Benefits of technology

It realizes spontaneous adhesion between particles and particles to the substrate, improves the mechanical stability and transparency of the coating, simplifies the preparation process, is suitable for large-scale production, and expands the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a rapid preparation technology for preparing a high-strength and high-transparency super-hydrophobic coating based on self-adhesive nanoparticles. The self-adhesive nanoparticles are composed of nanoparticles and a hydrophobic self-adhesive polymer. The high-strength and high-transparency super-hydrophobic coating is prepared on the surface of a transparent substrate through a spraying preparation technology. The specific process conditions of the technology comprise the following aspects: the mass ratio of the nanoparticles to the polymer in the self-adhesive nanoparticles, the stirring time, the stirring speed, the stirring speed, the stirring speed and the stirring speed. The method comprises the following steps: preparing a spraying solution, the composition of the spraying solution, the concentration of a polymer in the hydrophobic self-adhesion nanoparticles, the concentration of organic acid, the moving speed of a spraying gun, the pressure of the spraying gun, the number of spraying layers, the spraying flow, the distance from the spraying gun to a substrate, and the temperature and time of spraying post-treatment. The prepared coating has good super-hydrophobic performance, excellent mechanical strength and good transparency, and the rapid preparation technology can solve the technical bottlenecks that an existing transparent super-hydrophobic coating is poor in mechanical strength and tedious in preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a super hydrophobic coating with high mechanical strength and high transparency prepared by using designed self-adhesive nanoparticles and a rapid preparation technology thereof. Background Art

[0002] Since the micron-scale papillae and nano-scale wax crystal structures on the surface of lotus leaves were observed by electron microscopy in the 20th century, superhydrophobic surfaces have received widespread attention in many fields. Their superhydrophobicity is due to the low surface energy materials and the micro-nano structures on the surface. In the late 20th century, artificially prepared superhydrophobic surfaces developed rapidly. The methods used to obtain superhydrophobic surfaces can be divided into two categories: (1) introducing a wide range of nano- and / or micro-scale roughness on hydrophobic materials with low surface free energy. (2) modifying the previous micro / nanostructure rough surface by coating a hydrophobic layer with low surface free energy. Combining superhydrophobic coatings with transparency can greatly improve the application of superhydrophobic surfaces in optical and electronic devices, such as solar panels, automotive glass, goggles, smart windows, camera lenses and electronic screens. This transparent self-cleaning surface represents one of the key development directions of future optical / electronic devices (Journal of Materials Chemistry A, 2013, 1: 4146-4161).

[0003] In the past few decades, people have used a variety of nanostructures such as nanoparticles, carbon nanotubes (CNTs) and nanosheets to prepare transparent super-hydrophobic coatings. However, there is no strong chemical bonding between the nanoparticles, and the adhesion between the particles and the substrate is weak, resulting in poor mechanical durability of the coating; under very small loads, the coating will be damaged or broken, resulting in loss of hydrophobicity (ACS Applied Materials & Interfaces, 2023, 15 (34): 40913-40922). In order to give the silica coating mechanical durability, there are currently several main methods for enhancing the mechanical stability of super-hydrophobic coatings: (1) "Armor" structure introduction: through the design and construction of a layered structure, the microstructure is built on the surface of the coating, which can resist most external damage, and then the nanostructure is introduced into the cavity of the microstructure to provide buffering and protection for the fragile nanostructure. For example, Wang et al. proposed an "armor" strategy. Using photoetching technology, they made an inverted pyramid-shaped microcavity structure on a silicon wafer. These microcavities are then filled with SiO 2Nanoparticles, ultimately producing an "armored" superhydrophobic surface (Nature, 2020, 582(7810): 55-59). (2) Introducing adhesives or crosslinking agents: Introducing adhesives to enhance the interfacial interaction between the nanocoating and the substrate can also achieve adhesion between particles and between particles and the substrate, thereby improving the mechanical stability of the superhydrophobic surface. The preparation method of a transparent superhydrophobic coating is simple and cost-effective, and is formed by spraying, dipping, spin coating, or deposition on various target substrates by ultrasonic technology. Zhongfeng Ji et al. took advantage of the high transparency and good adhesion of epoxy resin, which can stably combine silicon particles with the substrate to ensure the stability of the coating. First, the silica nanoparticles were hydrophobically modified, and the curing agent (D-400) was added to the epoxy resin (E-51) and stirred evenly at 80°C. After heating at 80°C for 90 minutes, the preheated glass plate coated with epoxy resin was placed in a container filled with 50°C warm water. Next, modified silicon particles of different mass fractions are added, mixed with warm water and slowly stirred to form a uniform film. After removing the moisture, this uniform film is deposited on the semi-cured epoxy resin. Finally, the coating is kept at 80°C for 60 minutes to complete the curing process. The WCA of the obtained coating is as high as 160° and the SA is less than 2° (Chemical Engineering Journal, 2021, 404: 126456-126462). The bonding between particles is achieved by introducing a cross-linking agent through chemical bonds: first, the substrate surface is treated to form a reaction site, and then a cross-linking agent is added to enhance the interface interaction between the coating and the substrate, and finally a high-temperature heating and curing is performed to obtain a super-hydrophobic coating with high mechanical strength. As reported in the CN 113684724B patent, the polydimethylsiloxane containing a curing agent is dissolved and infiltrated into 10-undecenoic acid cellulose ester coated paper by reverse penetration, and then a super-stable super-hydrophobic coating is prepared by thermal curing (temperature of 90-150°C), and high-temperature treatment is required to obtain a durable super-hydrophobic coating.

[0004] The above methods still have certain problems: the method of introducing an "armor" structure to protect nanoparticles has problems such as large equipment size and complex operation; the method of introducing an adhesive requires steps such as hydrophobic modification of the coating / particles, thermal curing and cross-linking of the coating, and high-temperature treatment. The coating preparation process is cumbersome and time-consuming and cannot meet the needs of large-scale production; secondly, the adhesives used, such as epoxy resins and polyurethanes, are easy to wrap nanoparticles, block the micro-nano pores between nanoparticles, and affect the transparency of the coating (Advanced Engineering Materials, 2023, 25(6): 1438-1656).

[0005] In view of the above problems, the present invention starts with the basic building block unit of the coating and designs and prepares hydrophobic nanoparticles with self-adhesiveness. By giving the building block particles spontaneous adhesion, the particle-particle and particle-substrate forces in the super-hydrophobic coating can be effectively enhanced, and the mechanical stability of the coating can be improved; the nano-void structure in the coating is retained, and the low refractive index and high transparency of the coating are effectively guaranteed. In addition, a spraying process based on self-adhesive nanoparticles is developed to prepare a high-strength, highly transparent super-hydrophobic coating. Summary of the invention

[0006] The purpose of the present invention is to design a kind of spontaneously adhering nanoparticles for constructing super-hydrophobic coatings, which is different from the traditional nano-coating preparation method that requires the additional addition of binders, and to provide a rapid preparation technology to solve the technical bottlenecks of the existing super-hydrophobic coatings, such as poor mechanical strength, poor transparency and complicated preparation process.

[0007] In order to achieve the above object, the present invention adopts the following technical scheme:

[0008] By preparing a self-adhesive nanoparticle, including a nanoparticle body and a hydrophobic-self-adhesive polymer that adheres to the surface of the nanoparticle, the obtained nanoparticle has spontaneous adhesion and hydrophobicity, and can achieve spontaneous adhesion between particles and between particles and substrates. The self-adhesive nanoparticles form a spray liquid in a solvent, and a super-hydrophobic coating is prepared on a variety of transparent substrates using a spraying process, thereby achieving rapid preparation of a high-strength super-hydrophobic coating.

[0009] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, which is characterized in that the self-adhesive nanoparticles are composed of nanoparticles and hydrophobic self-adhesive polymers; the polymers adhere to the surfaces of the nanoparticles, a large number of dopamine groups adhere to the surfaces of the particles, the polymers and the particles, as well as the particles themselves, are connected through hydrogen bonds and hydrophobic interactions, specifically, the polymer molecules rapidly and autonomously adhere to the surfaces of the particles through the above interactions, the particles acquire self-adhesion, and the self-adhesive particles bond to each other.

[0010] The invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the main nanoparticles of the self-adhesive nanoparticles are selected from one of silicon dioxide nanoparticles, titanium dioxide nanoparticles, and aluminum oxide nanoparticles, because the catechol structure of the polymer in the self-adhesive nanoparticles can drive the polymer to adhere to the surface of various materials;

[0011] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the structural unit of the hydrophobic-self-adhesive polymer in the self-adhesive nanoparticles is as shown in formula (I);

[0012]

[0013] Wherein, R is -H, -OH, -COOH; x, y are positive integers, and 1≤x≤5000, 1≤y≤5000, x:y=4:1~1:4; -C n F 2n+1 Where n is a positive integer, which is 3, 5, 9, 13, 15, 17;

[0014] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the preparation of the self-adhesive nanoparticles is prepared by dispersing a hydrophobic polymer in a nanoparticle solution, the mass ratio of silicon dioxide to polymer is (0.5-50):1, the stirring time is 10-60 minutes, and the stirring speed is 500-1000rpm;

[0015] The present invention relates to a rapid preparation technology for preparing a high-strength, transparent, super-hydrophobic coating based on self-adhesive nanoparticles, which is characterized by: preparing a high-strength, high-transparency, super-hydrophobic coating on the surface of a transparent substrate by spraying preparation technology;

[0016] The invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the spray preparation technology is universal and can be used to prepare super-hydrophobic coatings on the surfaces of various transparent materials. The dopamine groups on the surface of the self-adhesive nanoparticles can adhere to different substrates through various interactions such as hydrogen bonding, cation-π, π-π stacking, hydrophobic interactions, etc. The transparent substrate can be selected from PMMA, PET, glass sheets, PVC, etc.

[0017] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, which is characterized in that: the self-adhesive nanoparticles form a spray liquid in a solvent, and the spray liquid consists of a solvent, hydrophobic self-adhesive nanoparticles, and an organic acid;

[0018] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the solvent selected in the spraying liquid is one of methanol, ethanol, and acetone, and the organic acid selected is one of acetic acid, sulfonic acid, and citric acid;

[0019] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the concentration of the polymer in the hydrophobic self-adhesive nanoparticles is 0.5-15 mg / mL, and the concentration of the organic acid is 0.58-580 mM;

[0020] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the moving speed of the spray gun is selected to be 3 to 10 cm / s;

[0021] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, which is characterized by: selecting the number of layers sprayed by the spray gun to be 5 to 30 layers;

[0022] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the distance between the spray gun and the substrate is selected to be 5 to 30 cm;

[0023] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the flow rate of the spray gun spraying is selected to be 0.2-1.0 mL / s;

[0024] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the pressure of the spray gun is selected to be 0.1-1.0 MPa;

[0025] The present invention relates to a rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles, characterized in that: the curing temperature of the coating is 40 to 60° C.; the curing time of the coating is 10 to 120 minutes;

[0026] The present invention has the following advantages:

[0027] (1) Self-adhesive nanoparticles have rapid spontaneous adhesion, which can achieve adhesion between particles and between particles and substrates. There is no need to add traditional cross-linking agents, which avoids tedious steps such as high-temperature post-treatment and the problem of reduced transmittance caused by clogging of nanopores.

[0028] (2) The spraying liquid prepared by the self-adhesive nanoparticles of the present invention is easy to prepare, the coating preparation process is simple, and it is suitable for large-scale production.

[0029] (3) The super-hydrophobic coating prepared by the self-adhesive nanoparticles of the present invention can be applied to multiple substrates and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0031] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0032] Figure 1 is a particle size distribution diagram of the self-adhesive nanoparticles in the solvent in the self-adhesive nanoparticle solution of Examples 1-6 of the present invention;

[0033] Figure 2 This is a scanning electron microscopic image of the high-strength, high-transparency super-hydrophobic coating prepared in Examples 1-3 of the present invention;

[0034] Figure 3 is the light transmittance of the high-strength, highly transparent super-hydrophobic coating prepared in Examples 1-3 of the present invention;

[0035] Figure 4 The water contact angle of the coating constructed by the self-adhesive nanoparticles of Examples 1-3 of the present invention before and after being adhered by tape;

[0036] Figure 5 is the water contact angle of the coating prepared in Examples 7-12 of the present invention;

[0037] Figure 6 is the water contact angle of the coating prepared in Examples 13, 14 and 15 of the present invention. DETAILED DESCRIPTION

[0038] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0039] Example 1

[0040] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-1 (molecular structure see Table 1, x:y = 3:7) is dispersed in an anhydrous ethanol solution of silica nanoparticles, the mass ratio of silica nanoparticles to Ⅱ-1 polymer is 3:1, and stirred at a stirring speed of 800rpm for 30min. Self-adhesive nanoparticles are obtained. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 8nm, and the particle size distribution diagram is a single peak (see Appendix for reference Figure 1 a).

[0041] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 7.5 mg / mL, and the acetic acid concentration is 5.8 mM. A high mechanical strength and high transparency super hydrophobic coating is prepared on a glass substrate by spraying technology, and the spraying conditions are as follows: the distance between the spray gun and the substrate is 15 cm, the horizontal moving speed is 10 cm / s, the spray gun pressure is 0.8 MPa, the flow rate is 0.8 ml / s, the number of spray layers is 5, and the sprayed coating is cured at 50°C for 30 minutes, and the temperature is lowered to room temperature to obtain the high strength and high transparency super hydrophobic coating of the present invention.

[0042] The scanning electron microscope image of the coating shows a nanoporous structure with many protrusions and depressions, and a large number of holes and grooves formed by nanoparticles, and the particles are not wrapped (see Figure 2 ) The average light transmittance of the coating was 92% (see Figure 3 ), through the water contact angle test, the water contact angle of the coating is 152°, and the water contact angle before and after the 3M tape adhesion becomes 149° (see attached for reference Figure 4 ).

[0043] Example 2

[0044] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive compound Ⅱ-2 (molecular structure see Table 1, x:y = 1:4) is dispersed in an anhydrous ethanol solution of silica nanoparticles, the mass ratio of silica nanoparticles to Ⅱ-2 polymer is 50:1, and stirred at a stirring speed of 500rpm for 60min to obtain self-adhesive nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 10nm, and the particle size distribution is a single peak. (See Figure 1 a).

[0045] Self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 3.5 mg / mL, and the sulfonic acid concentration is 5.8 mM. A high mechanical strength and high transparency super hydrophobic coating is prepared on a glass substrate by spraying technology, and the spraying conditions are as follows: the distance between the spray gun and the substrate is 30 cm, the horizontal movement speed of the spray gun is 10 cm / s, the spray gun pressure is 0.5 MPa, 5 layers are sprayed, the spray flow rate is 0.5 ml / s, and the sprayed coating is cured at 40° C. for 60 minutes. After cooling to room temperature, the high-strength and high-transparency super hydrophobic coating involved in the present invention is obtained.

[0046] The scanning electron microscope image of the coating shows a nanoporous structure with many protrusions and depressions, and a large number of holes and grooves formed by nanoparticles, and the particles are not wrapped (see Figure 2 ), the average light transmittance of the coating is 90% (see Figure 3), through the water contact angle test, the water contact angle of the coating is 147°, and after being adhered with 3M tape, the water contact angle of the coating becomes 142° (see attached for reference Figure 4 ).

[0047] Example 3

[0048] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-3 (molecular structure see Table 1, x:y = 1:1) is dispersed in an anhydrous ethanol solution of silica nanoparticles, the mass ratio of silica nanoparticles to Ⅱ-3 polymer is 0.5:1, and stirred at a stirring speed of 1000rpm for 20min to obtain self-adhesive nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 7nm, and the distribution appears outside 200nm, and the particle size distribution is wide. (See attached for reference Figure 1 a).

[0049] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 15 mg / mL, and the acetic acid concentration is 580 mM. A high mechanical strength and high transparency super hydrophobic coating is prepared on a glass substrate by spraying technology, and the spraying process is as follows: the distance between the spray gun and the substrate is 5 cm, the horizontal movement speed of the spray gun is 3 cm / s, the spray gun pressure is 0.2 MPa, 15 layers are sprayed, the spray flow rate is 0.25 ml / s, and the sprayed coating is cured at 60°C for 40 minutes, and the high strength and high transparency super hydrophobic coating of the present invention is obtained after cooling to room temperature.

[0050] Scanning electron microscopy images of the coating showed a rough structure, but with a lot of agglomeration between the nanoparticles (see Figure 2 ), the average light transmittance of the coating was 69% (see Figure 3 ) is translucent. Through the water contact angle test, the water contact angle of the coating is 137°. After being adhered with 3M tape, the water contact angle of the coating becomes 125° (see attached for reference). Figure 4 ).

[0051] Example 4

[0052] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: The preparation method of the hydrophobic-self-adhesive nanoparticle spray liquid is to disperse the hydrophobic-self-adhesive polymer Ⅱ-4 (molecular structure see Table 1, x:y = 4:1) in an anhydrous ethanol solution of aluminum oxide nanoparticles, the mass ratio of aluminum oxide nanoparticles to Ⅱ-4 polymer is 5:1, and stir at a stirring speed of 800rpm for 30 minutes to obtain self-adhesive nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 22nm, and the particle size distribution is a single peak. (See attached for reference Figure 1 b).

[0053] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 8 mg / mL, the sulfonic acid concentration is 58 mM, and a high-strength, high-transparency super-hydrophobic coating is prepared on a glass substrate by spraying technology. The spraying process is as follows: the spraying distance from the substrate is 5 cm, the horizontal moving speed is 5 cm / s, the spray gun pressure is 0.4 MPa, and the flow rate is 0.5 ml / s. Spray 5 layers, the sprayed coating is cured at 40°C for 60 minutes, and the temperature is lowered to room temperature to obtain the high-strength, high-transparency super-hydrophobic coating of the present invention. The coating is tested for a water contact angle, and the water contact angle of the coating is 150°.

[0054] Example 5

[0055] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: The preparation method of the hydrophobic-self-adhesive nanoparticle spray liquid is to disperse the hydrophobic-self-adhesive polymer Ⅱ-5 (molecular structure see Table 1, x:y = 1:4) in an anhydrous ethanol solution of aluminum oxide nanoparticles, the mass ratio of aluminum oxide nanoparticles to Ⅱ-5 polymer is 1:1, and stir at a stirring speed of 500rpm for 60min to obtain self-adhesive nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 20nm, and a broad peak appears outside 500nm, and the particle size distribution is wide. (See attached for reference Figure 1 b).

[0056] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 2.5 mg / mL, the acetic acid concentration is 58 mM, and a high-strength, high-transparency super-hydrophobic coating is prepared on a glass substrate by spraying technology. The spraying process is as follows: the spraying distance from the substrate is 15 cm, the horizontal moving speed is 3 cm / s, the pressure is 1 MPa, the spray gun flow rate is 0.8 ml / s, and 15 layers are sprayed. The sprayed coating is cured at 40°C for 20 minutes, and the temperature is lowered to room temperature to obtain the high-strength, high-transparency super-hydrophobic coating of the present invention. The coating is tested for a water contact angle, and the water contact angle of the coating is 150°.

[0057] Example 6

[0058] A rapid preparation technology for preparing high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-6 (molecular structure see Table 1, x:y = 7:3) is dispersed in anhydrous ethanol solution of aluminum oxide nanoparticles, the mass ratio of aluminum oxide nanoparticles to Ⅱ-6 polymer is 15:1, and stirred at a stirring speed of 800rpm for 40min. Self-adhesive nanoparticles are obtained. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 20nm, and the particle size distribution is a single peak. (See Appendix for reference) Figure 1 b).

[0059] The self-adhesive nanoparticles form a spray liquid in a solvent, and the polymer concentration in the spray liquid is 5.5mg / mL, and the sulfonic acid concentration is 0.58mM. By spraying technology, a high mechanical strength and high transparency super hydrophobic coating is prepared on a PVC substrate, and the spraying process is as follows: the spraying distance from the substrate is 20cm, the horizontal moving speed is 6cm / s, the pressure is 0.6MPa, and the spray gun flow rate is 0.5ml / s to spray 10 layers, and the sprayed coating is cured at 40°C for 40min, and the high-strength and high-transparency super hydrophobic coating involved in the present invention is obtained by cooling to room temperature. The coating is tested for water contact angle, and the water contact angle of the coating is 140°.

[0060] Example 7

[0061] A rapid preparation technology for preparing high-strength transparent super-hydrophobic coatings based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-7 (molecular structure see Table 1, x:y=7:3) is dispersed in a methanol solution of titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles to Ⅱ-7 polymer is 3:1, and the mixture is stirred at a stirring speed of 1000 rpm for 40 minutes to obtain hydrophobic nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 15 nm, and the particle size distribution is a single peak.

[0062] The self-adhesive nanoparticles are formed into a spray liquid in a solvent, the polymer concentration in the spray liquid is 6 mg / mL, the sulfonic acid concentration is 0.58 mM, and a high mechanical strength and high transparency super hydrophobic coating is prepared on a PVC substrate by spraying technology. The spraying conditions are as follows: the spraying distance from the substrate is 30 cm, the horizontal moving speed is 8 cm / s, the pressure is 0.6 MPa, the spray gun flow rate is 0.5 ml / s, and 15 layers are sprayed. The sprayed coating is cured at 40 ° C for 20 minutes and cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating of the present invention. The water contact angle of the coating is tested, and the water contact angle of the coating is 161° (see attached for reference Figure 6 a).

[0063] Example 8

[0064] A rapid preparation technology for preparing high-strength transparent super-hydrophobic coatings based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-8 (molecular structure see Table 1, x:y=1:4) is dispersed in an anhydrous methanol solution of titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles to Ⅱ-8 polymer is 10:1, and the mixture is stirred at a stirring speed of 1000 rpm for 15 minutes to obtain self-adhesive nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 17 nm, and the particle size distribution is a single peak.

[0065] The self-adhesive nanoparticles form a spray liquid in a solvent, and the polymer concentration in the spray liquid is 9.5 mg / mL and the acetic acid concentration is 58 mM. By spraying technology, a high mechanical strength and high transparency super hydrophobic coating is prepared on a PET substrate, and the spraying conditions are as follows: the spraying distance from the substrate is 25 cm, the horizontal moving speed is 8 cm / s, the pressure is 1 MPa, and the spray gun flow rate is 1 ml / s for spraying 15 layers. The sprayed coating is cured at 40 ° C for 120 min, and the temperature is cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating involved in the present invention. The coating is tested for water contact angle, and the water contact angle of the coating is 137 ° (see attached for reference Figure 6 b).

[0066] Example 9

[0067] A rapid preparation technology for preparing high-strength transparent super-hydrophobic coatings based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-9 (molecular structure see Table 1, x:y=1:1) is dispersed in an anhydrous methanol solution of titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles to Ⅱ-9 polymer is 1:1, and the mixture is stirred at a stirring speed of 500 rpm for 60 minutes to obtain self-adhesive nanoparticles. Compared with the original nanoparticles, the average particle size of the self-adhesive nanoparticles after adding the polymer increases by 12 nm, and the particle size distribution is a single peak.

[0068] The self-adhesive nanoparticles are formed into a spray liquid in a solvent, the polymer concentration in the spray liquid is 7.5 mg / mL, the acetic acid concentration is 5.8 mM, and a high mechanical strength and high transparency super hydrophobic coating is prepared on a glass substrate by spraying technology. The spraying conditions are as follows: the spraying distance from the substrate is 15 cm, the horizontal moving speed is 3 cm / s, the spray gun pressure is 0.4 MPa, the flow rate is 0.5 ml / s, 20 layers are sprayed, and the sprayed coating is cured at 50°C for 100 minutes, and the temperature is cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating of the present invention. The water contact angle test of the coating is performed, and the water contact angle of the coating is 148° (see attached for reference). Figure 5 c).

[0069] Example 10

[0070] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-10 (molecular structure see Table 1, x:y=7:3) is dispersed in an anhydrous ethanol solution of aluminum oxide nanoparticles, the mass ratio of aluminum oxide nanoparticles to Ⅱ-10 polymer is 5:1, and the mixture is stirred at a stirring speed of 800 rpm for 30 minutes to obtain self-adhesive nanoparticles.

[0071] The self-adhesive nanoparticles are formed into a spray liquid in a solvent, the polymer concentration in the spray liquid is 5 mg / mL, the citric acid concentration is 58 mM, and a high mechanical strength and high transparency super hydrophobic coating is prepared on a PVC substrate by spraying technology. The spraying conditions are as follows: the distance between the spray gun and the substrate is 16 cm, the horizontal moving speed is 5 cm / s, the spray gun pressure is 0.6 MPa, the flow rate is 0.6 ml / s, 5 layers are sprayed, and the sprayed coating is cured at 40°C for 30 minutes, and cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating of the present invention. The water contact angle test of the coating is 150° (see attached for reference). Figure 5 d).

[0072] Embodiment 11

[0073] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-11 (molecular structure see Table 1, x:y=3:7) is dispersed in an anhydrous methanol solution of titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles to Ⅱ-11 polymer is 10:1, and the mixture is stirred at a stirring speed of 600 rpm for 20 minutes to obtain self-adhesive nanoparticles.

[0074] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 11 mg / mL, the sulfonic acid concentration is 0.58 mM, and a high mechanical strength and high transparency super hydrophobic coating is prepared on a PMMA substrate by spraying technology. The spraying conditions are as follows: the distance between the spray gun and the substrate is 15 cm, the horizontal moving speed is 10 cm / s, the spray gun pressure is 0.6 MPa, the flow rate is 0.6 ml / s, 10 layers are sprayed, and the sprayed coating is cured at 40°C for 20 minutes, and cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating of the present invention. The water contact angle test of the coating is 152° (see attached for reference). Figure 5 e).

[0075] Example 12

[0076] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-12 (molecular structure see Table 1, x:y=7:3) is dispersed in an anhydrous ethanol solution of silica nanoparticles, the mass ratio of silica nanoparticles to Ⅱ-12 polymer is 20:1, and the mixture is stirred at a stirring speed of 500 rpm for 50 minutes to obtain self-adhesive nanoparticles.

[0077] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 15 mg / mL, and the acetic acid concentration is 5.8 mM. A high mechanical strength and high transparency super hydrophobic coating is prepared on a PET substrate by spraying technology, and the spraying process is as follows: the distance between the spray gun and the substrate is 15 cm, the horizontal moving speed is 6 cm / s, the spray gun pressure is 0.6 MPa, and the flow rate is 0.6 ml / s. 20 layers are sprayed, and the sprayed coating is cured at 40°C for 10 minutes, and the temperature is lowered to room temperature to obtain the high-strength and high-transparency super hydrophobic coating of the present invention, and the water contact angle of the coating is 120°.

[0078] (See attached for reference Figure 5 f).

[0079] Example 13

[0080] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-1 (molecular structure see Table 1, x:y = 1:4) is dispersed in an anhydrous ethanol solution of silica nanoparticles, the mass ratio of silica nanoparticles to Ⅱ-1 polymer is 2:1, and the mixture is stirred at a stirring speed of 600 rpm for 20 minutes to obtain self-adhesive nanoparticles.

[0081] The self-adhesive nanoparticles form a spray liquid in a solvent, and the polymer concentration in the spray liquid is 10.5 mg / mL, and the citric acid concentration is 580 mM. By spraying technology, a high mechanical strength and high transparency super hydrophobic coating is prepared on a PET substrate, and the spraying process is as follows: the distance between the spray gun and the substrate is 30 cm, the horizontal moving speed is 1 cm / s, the pressure is 0.5 MPa, the spray gun flow rate is 0.5 ml / s, the number of spray layers is 25 layers, and the sprayed coating is cured at 60 ° C for 60 min, and the high strength and high transparency super hydrophobic coating involved in the present invention is obtained by cooling to room temperature. The coating is tested for water contact angle, and the water contact angle of the coating is 154 ° (see attached for reference Figure 6 a).

[0082] Embodiment 14

[0083] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: a hydrophobic-self-adhesive polymer II-8 (molecular structure see Table 1, x:y=1:4) is dispersed in an anhydrous ethanol solution of silica nanoparticles, the mass ratio of silica nanoparticles to II-8 polymer is 5:1, and the mixture is stirred at a stirring speed of 800 rpm for 30 minutes to obtain self-adhesive nanoparticles.

[0084] The self-adhesive nanoparticles form a spray liquid in a solvent, the polymer concentration in the spray liquid is 1.5 mg / mL, the acetic acid concentration is 58 mM, and a high mechanical strength and high transparency super hydrophobic coating is prepared on a PVC substrate by spraying technology. The spraying conditions are as follows: the distance between the spray gun and the substrate is 20 cm, the horizontal moving speed is 3 cm / s, the pressure is 0.5 MPa, the spray gun flow rate is 0.5 ml / s, and 15 layers are sprayed. The sprayed coating is cured at 50 ° C for 80 minutes, and the temperature is cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating of the present invention. The water contact angle test of the coating is 150 ° (see the attached reference) Figure 6 b).

[0085] Embodiment 15

[0086] A rapid preparation technology for preparing a high-strength transparent super-hydrophobic coating based on self-adhesive nanoparticles is as follows: the hydrophobic-self-adhesive polymer Ⅱ-9 (molecular structure see Table 1, x:y=4:1) is dispersed in a methanol solution of titanium dioxide nanoparticles, the mass ratio of titanium dioxide nanoparticles to Ⅱ-9 polymer is 4:1, and the mixture is stirred at a stirring speed of 600 rpm for 60 minutes to obtain self-adhesive nanoparticles.

[0087] The self-adhesive nanoparticles form a spray liquid in a solvent, and the polymer concentration in the spray liquid is 10 mg / mL and the sulfonic acid concentration is 0.58 mM. By spraying technology, a high mechanical strength and high transparency super hydrophobic coating is prepared on a PMMA substrate, and the spraying conditions are as follows: the distance between the spray gun and the substrate is 10 cm, the horizontal moving speed is 8 cm / s, the pressure is 0.8 MPa, and the spray gun flow rate is 0.6 ml / s to spray 15 layers, and the sprayed coating is cured at 60 ° C for 20 min, and cooled to room temperature to obtain the high-strength and high-transparency super hydrophobic coating involved in the present invention. The coating is tested for water contact angle, and the water contact angle of the coating is 142 °.

[0088] Table 1 Summary of the structural formulas of hydrophobic polymers used in Examples 1-15

[0089]

Claims

1. Its characteristics are: The high-strength and high-transparency super-hydrophobic coating is composed of hydrophobic self-adhesive nanoparticles.

2. The hydrophobic self-adhesive nanoparticles according to claim 1, characterized in that: It is composed of nanoparticles and hydrophobic self-adhesive polymers.

3. The nanoparticle according to claim 2, characterized in that: It is one of silicon dioxide nanoparticles, titanium dioxide nanoparticles and aluminum oxide nanoparticles.

4. The hydrophobic self-adhesive polymer according to claim 2, characterized in that: It is composed of units of formula (I); Wherein, R is -H, -OH, -COOH; x, y are positive integers, and 1≤x≤5000, 1≤y≤5000, x:y=4:1~1:4; -C n F 2n+1 The n in it is a positive integer, which can be 3, 5, 9, 13, 15, 17.

5. The hydrophobic self-adhesive nanoparticles according to claim 2, characterized in that: The hydrophobic polymer is dispersed in the nanoparticle solution, the mass ratio of the nanoparticles to the polymer is (0.5-50):1, the stirring time is 10-60 minutes, and the stirring speed is 500-1000 rpm.

6. The high-strength, high-transparency, super-hydrophobic coating rapid preparation technology according to claim 1, characterized in that: A high-strength and high-transparency super-hydrophobic coating is prepared on the surface of a transparent substrate through spraying preparation technology.

7. The spraying preparation technology according to claim 6, characterized in that: The transparent substrate is one of glass, PMMA, PET and PVC.

8. The spraying preparation technology according to claim 6, characterized in that: The spraying liquid consists of a solvent, hydrophobic self-adhesive nanoparticles and an organic acid.

9. The spraying liquid according to claim 8, characterized in that: The solvent is one of methanol, ethanol and acetone, the organic acid is one of acetic acid, sulfonic acid, lactic acid and citric acid, the concentration of the polymer in the hydrophobic self-adhesive nanoparticles is 0.5-15 mg / ml, and the concentration of the organic acid is 0.58-580 mM.

10. The spraying preparation technology according to claim 6, characterized in that: The moving speed of the spray gun is 3 to 10 cm / s, the pressure of the spray gun is 0.1 to 1 MPa, the number of spray layers is 5 to 30 layers, the spray flow rate is 0.2 to 1.0 mL / s, and the distance between the spray gun and the substrate is 5 to 30 cm; after spraying, the substrate is placed at a constant temperature of 40 to 60° C. for 10 to 120 minutes.

Citation Information

Patent Citations

  • Preparation method and application of self-assembled functional coating based on low-surface-energy nanoparticles

    CN116082864A

  • Coating compositions, processes, and applications for low friction and high durability substrates

    US20210163776A1